2019
DOI: 10.1103/physrevb.100.214401
|View full text |Cite
|
Sign up to set email alerts
|

Origin of up-up-down-down magnetic order in Cu2GeO4

Abstract: We use density-functional band-structure calculations to explore the origin of the up-up-downdown (UUDD) magnetic order in Cu2GeO4 with the frustrated J1 − J2 spin chains coupled into layers within the spinel-like crystal structure. In contrast to earlier studies, we find that the nearestneighbor coupling J1 may be negligibly small, owing to a nearly perfect compensation of the ferromagnetic direct exchange and antiferromagnetic superexchange. Under this condition, weak symmetric anisotropy of the exchange cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…This is illustrated by the example of K 2 IrCl 6 , where the space group and Wyckoff site of the magnetic Ir 4+ (d 4 ) ions are the same as in Ba 2 YReO 6 , and which shows drastic (up to 50%) departures from the dipolar approximation even at κ ∼ 1 Å −1 [29]. We attempt to account for these effects by calculating the j 0 (κ ) contribution to the dipolar form factor by Fourier transforming the moment density obtained by density functional theory [30]; see also [31][32][33][34][35][36][37][38]. The delocalization of spin density onto the O 2− surrounding the Re 5+ leads to a sharper drop in f (κ ) with increasing κ than in the free-ion case.…”
Section: Form Factor and Ordered Momentmentioning
confidence: 99%
“…This is illustrated by the example of K 2 IrCl 6 , where the space group and Wyckoff site of the magnetic Ir 4+ (d 4 ) ions are the same as in Ba 2 YReO 6 , and which shows drastic (up to 50%) departures from the dipolar approximation even at κ ∼ 1 Å −1 [29]. We attempt to account for these effects by calculating the j 0 (κ ) contribution to the dipolar form factor by Fourier transforming the moment density obtained by density functional theory [30]; see also [31][32][33][34][35][36][37][38]. The delocalization of spin density onto the O 2− surrounding the Re 5+ leads to a sharper drop in f (κ ) with increasing κ than in the free-ion case.…”
Section: Form Factor and Ordered Momentmentioning
confidence: 99%
“…where t ij is the hopping integral between the ith and jth Wannier functions. On the basis of these Wannier functions, one can perform a microscopic analysis of the exchange interactions by using a superexchange theory approach 29 :…”
Section: Computational Methods and Modelsmentioning
confidence: 99%
“…(4). The former involves a significant error bar when calculated by DFT 29 , but its microscopic origin is well known and for cuprates it comes from the Hund's coupling on the ligand site 37 . The size of J F depends on the contribution of the ligand orbitals to the Cu d x 2 −y 2 Wannier function 37 .…”
Section: B Pressure Evolutionmentioning
confidence: 99%
“…Correlation effects were taken into account on the static mean-field level using the DFT+U method 35 , where we considered an effective on-site Coulomb U and Hund's exchange J H interactions in the rotationally invariant form 36 . A value of J H = 1 eV can be used for compounds with 3d orbitals 37,38 , while the on-site Coulomb parameter depends on the specific system. Previous results showed that the best agreement with experiment can be obtained using a relatively small value of U = 2 eV 1,2,39 .…”
Section: B Computational Approachmentioning
confidence: 99%